(3dHGH GdJChjd aj eYGfj GdJfRjds - (3GdTjMj, CHh eMeO, GdNGRf, Ydj Hf eMeO Hf EHQGgje, J (B741 (3gs
(3ChdgG (B:s
(3JaSjQ ShQI GdCYQGa ecjI Qhj Pdc Yf GHf YHGSs
(3BNQgG (B:s
(3Yf GdfHj Udi Gddg Ydjg hSde bGd(B: (3ef MaX YTQ CjGJ ef Chd ShQI Gdcga YUe ef aJfI GdOLGds
(3JHUQI GdYfhGf (B:s
(3JaSjQ GdNGRfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5/5s
(3gOjI GdYGQajf (B1/718s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs